2015
DOI: 10.1080/09640568.2015.1009975
|View full text |Cite
|
Sign up to set email alerts
|

Understanding communicational behavior among rangelands’ stakeholders: application of social network analysis

Abstract: Understanding communicational behavior of rangelands' stakeholders is fundamental for effective development of rangeland management plans. This study aimed to understand differences between stakeholders' relations among various actors involved in rangeland management using social network analysis (SNA). A survey was conducted on 334 stakeholders (89 extension agents, 110 researchers and 135 executive agents) in the Tehran province, Iran. Results showed that all the three groups of stakeholders are interested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Borgatti et al (2018) posited that a social network refers to something active, alive and dynamic and can be quantified by SNA technique, allowing researchers to study how people are connected to each other and to explain relationships within a specified network. Relationships that occur in the social world are empirical social phenomena, whereby SNA offers researchers a particular analytical technique for measuring multiple aspects of the social dynamics that govern networks, including the social structure created by the existing relationship between social entities (Hosseininia et al, 2016;Mead, 2001). Additionally, Bright et al (2018) suggested that SNA is a "set of analytic techniques used to describe social groups by examining the actors in the groups and the connections between them" (p. 238), thereby, reinforcing the case for employing SNA to study social relationships.…”
Section: Social Network Analysismentioning
confidence: 99%
“…Borgatti et al (2018) posited that a social network refers to something active, alive and dynamic and can be quantified by SNA technique, allowing researchers to study how people are connected to each other and to explain relationships within a specified network. Relationships that occur in the social world are empirical social phenomena, whereby SNA offers researchers a particular analytical technique for measuring multiple aspects of the social dynamics that govern networks, including the social structure created by the existing relationship between social entities (Hosseininia et al, 2016;Mead, 2001). Additionally, Bright et al (2018) suggested that SNA is a "set of analytic techniques used to describe social groups by examining the actors in the groups and the connections between them" (p. 238), thereby, reinforcing the case for employing SNA to study social relationships.…”
Section: Social Network Analysismentioning
confidence: 99%
“…The social network analysis model can demonstrate the great potential to exam the behavior and interaction of various stakeholders [8]. SNA can be an efficient tool for assessing communication behavior in stakeholder management [9].SNA can make an important contribution, as interaction and dialogue between stakeholders is critical to improving decision-making and awareness on several topics [10]- [12] in [13].…”
Section: Social Network and Social Network Analysis (Sna)mentioning
confidence: 99%
“…In addition, the research on stakeholders has mostly adopted qualitative methods and lacks quantitative methods. Some scholars have used the association network method to quantitatively explore the complex interconnections among social phenomena, which provides a reference method for quantitatively exploring relationships among stakeholders [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%